Curcumin and its nano-formulations: Defining triple-negative breast cancer targets through network pharmacology, molecular docking, and experimental verification - Deng, Zhicheng; Chen, Guanghui; Shi, Yonghui; Lin, Ying; Ou, Jiebin; Zhu, Hua; Wu, Junyan; Li, Guocheng; Lv, Li (Frontiers in Pharmacology, 2022)
Background: Curcumin (CUR) displays the capability to suppress the proliferation and metastasis of various cancer cells. However, the effects and underline mechanisms of CUR to treat triple negative breast cancer (TNBC) have not been systematically elucidated with an appropriate method. Methods: In the present research, a combination method of network pharmacology, molecular docking and in vitro bio-experiment was used to investigate the pharmacological actions and underline mechanisms of CUR against TNBC. First, common targets of CUR and TNBC were screened via Venny 2.1.0 after potential CUR-related targets and targets of TNBC were got from several public databases. And then, the Gene Ontology (GO) function and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were performed in the Metascape website, and the network of compound-targets-pathways was constructed via Cytoscape software. Besides, the network of protein-protein interaction was constructed by STRING database to screen potential targets. Moreover, molecular docking was applied to affirm the interaction of CUR with the screened top 10 potential targets. Finally, in vitro experiments were used to further verify the effects and mechanisms of CUR and its nano-formulation (CUR-NPs) against TNBC. Results: 40 potential targets of CUR against TNBC were got. STAT3, AKT1, TNF, PTGS2, MMP9, EGFR, PPARG, NFE2L2, EP300 and GSK3B were identified as the top 10 targets of CUR against TNBC. In vitro experiment verified that CUR and CUR-NPs could not only restrain the invasion, migration and proliferation of MDA-MB-231 cells, but also induce their apoptosis. In addition, molecular docking demonstrated that CUR could bind spontaneously with the screened top 10 targeted proteins, and real-time PCR experiment demonstrated that both CUR and CUR-NPs could downregulate the genetic expression levels of the 10 targets. Moreover, according to the CUR-targets-pathways network, PI3K-Akt, EGFR tyrosine kinase inhibitor resistance, JAK-STAT, Foxo, and HIF-1 signaling pathway were identified as the important pathways of CUR effects on TNBC. Among them, the inhibiting effects of CUR and CUR-NPs on JAK-STAT signaling pathway were further verified by western blot analysis. Conclusion: Taken together, the present research demonstrates that CUR and CUR-NPs have pharmacological effects against TNBC via a multi-target and multi-pathway manner.